From inspiration to innovation: A mediated model of leadership and innovative behavior - Jadmiko, Purbo; Azliyanti, Elfitra; Wati, Linda; Novianti, Neva; Haikal, Muhammad (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2026)
This study investigates the effect of transformational leadership on innovative work behavior in higher education institutions, examining the mediating roles of knowledge sharing and motivation to learn. Data were collected from 150 full-time lecturers in public and private universities in Padang, Indonesia. Structural equation modeling (SEM) was employed to analyze both direct and indirect relationships among variables. The findings reveal that transformational leadership positively influences innovative work behavior directly and indirectly through knowledge sharing, confirming a partial mediation effect. However, motivation to learn does not significantly mediate this relationship, indicating its intrinsically driven nature. The study confirms the importance of leadership style and collaborative culture in fostering innovation among academic staff. Theoretically, the research enriches the understanding of psychological and social mechanisms linking leadership to innovation, particularly in the unique context of higher education. Practically, it offers insights for university leaders to cultivate a supportive environment that encourages knowledge sharing and intrinsic learning motivation, which are essential for sustaining innovation in academic settings.